Cryo-assisted resection of primary breast cancer en bloc and tumor cryoablation connected with local drug delivery and targeting of tumor fluids. Experimental and clinical studies - Korpan, M. M.; Xiao, Yueyong; He, Xiaofeng; Dronov, O. I. (General Surgery, 2023)
Objective — to use cryosurgery in combination with simultaneous peritumoral and intratumoral tracer injections of blue dye for further lymphatic mapping in the treatment of primary breast tumors. The effectiveness of intraoperative cryoprobe‑assisted injection of blue dye and cytotoxic‑tracer mixture for locoregional drug targeting in the VX2 tumor model as well as its translational significance for cryo‑assisted breast tumor surgery with blue dye alone were evaluated. Sentinel lymph node mapping, pathological determination of the tumor, and resection margins were achievable. Materials and methods. Thirty‑nine patients with primary breast cancer in stages I to IV, aged 52,4 (±19) years (mean, standard deviation (SD) years), were randomly selected, treated at the Rudolfinerhaus Private Clinic in Vienna, Austria, and included in this preliminary clinical study. Under computed tomography guidance, we injected 2 ml of cytotoxic‑tracer mixture in five aliquots into the margins of 16 frozen or normothermic VX2 tumors. We evaluated the intraoperative and post‑operative drug targeting and therapeutic efficacy at the tumor‑host interface by means of computer tomography, gross examination, and histopathology. In thirty‑four T1 to T4 primary breast cancers, we performed an ultrasound‑guided cryoprobe‑assisted tumor freezing‑thawing cycle, blue dye‑guided lymphatic mapping, and surgery. We examined an intraoperative and freshly resected specimen and the blue dye distribution pattern in the tumor‑host interface, lymph node(s), breast parenchyma, and resection cavity. Results. 29 of the 38 patients had localized primary breast cancer, which was estimated to be resectable without neoadjuvant chemotherapy. 87% of patients had one to twelve stained axillary lymph nodes, while 72% of patients had another quadrant and resection cavity stained. Fluid‑impervious frozen VX2 or breast tumors transported drug(s) in an arc‑like pattern at the tumor‑host interface regardless of freeze dose, number of freeze‑thaw cycles, drug dose fractionation, tumor characteristics, or tumor dimensions. During melting, the cytotoxic‑tracer mixture spread within 50% of the VX2 tumor and mirrored that of the tumor‑host interface; it was massive in normothermia. In VX2, the CT gap corresponded to 20% of the focal margin necrosis in pathology. In both studies, blue dye dose‑staining spread linearly in the tumor‑host interface and tumor. Conclusions. The study paves the way for intraoperative cryo‑assisted cure options for primary breast cancer. We have shown that our cryosurgical technique of repeatedly freezing deep tumors for en bloc resection or for in situ ablation of primary breast cancer, facilitated by IOUS monitoring, can be coupled with the simultaneous injection of dye tracers during conventional surgery, which then allows for lymphatic mapping. Intraoperative freezing‑assisted drug delivery and targeting techniques during cryoablation of the VX2 tumor translate successfully to locoregional blue dye targeting and lymphatic mapping during cryo‑assisted surgery of breast cancer. We explored the ability of our strategy to prevent tumor cell migration, but not that of injected tracers, to the lymphovascular drainage during conventional resection of frozen breast malignancies.